Zirconium and hafnium hydrazinediido half-sandwich complexes: synthesis and reactivity - Schweizer, Peter Dominik; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2014)
The hydrazinediido complexes [Cp*M(NxylN)(NNPh2)(dmap)] (M = Zr, 3a; M = Hf, 3b; NxylN = 2-(N-xylylamino)pyrrolinate) have been synthesized, and their reactivity has been investigated. Both complexes were prepared from [Cp*M(NxylN)Cl2] (1a,b) and [Cp*M(NxylN)(NHNPh2)Cl] (2a,b), respectively, as precursors.